2004
DOI: 10.1021/om0495325
|View full text |Cite
|
Sign up to set email alerts
|

Pt−Ag Catalyst System for Hydroarylations with Unactivated Arenes and Olefins

Abstract: A series of Pt complexes activated by Ag(I) salts have been shown to catalyze Markovnikov hydroarylations of unactivated olefins under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 23 publications
2
87
0
4
Order By: Relevance
“…21 Tilley, Bell, and Karshtedt found that a PtÀAg catalyst system and Pt(II) catalysts supported by pyridylÀpyrrolyl ligands initiate norbornene hydroarylation, but the observed product selectivity suggests the possibility of a FriedelÀCrafts-type pathway. 22,29 Particularly germane is a recent study that reveals catalytic olefin hydroarylation using Pt(II) triflate salts likely proceeds by formation of triflic acid, which serves as the active catalyst. 30 Our groups reported a series of studies on TpRu(L)(NCMe)-(Ph) [Tp = hydridotris(pyrazolyl)borate, L = CO, PMe 3 , P(Npyrrolyl) 3 , or P(OCH 2 ) 3 CEt] catalysts for olefin hydroarylation.…”
Section: à26mentioning
confidence: 99%
“…21 Tilley, Bell, and Karshtedt found that a PtÀAg catalyst system and Pt(II) catalysts supported by pyridylÀpyrrolyl ligands initiate norbornene hydroarylation, but the observed product selectivity suggests the possibility of a FriedelÀCrafts-type pathway. 22,29 Particularly germane is a recent study that reveals catalytic olefin hydroarylation using Pt(II) triflate salts likely proceeds by formation of triflic acid, which serves as the active catalyst. 30 Our groups reported a series of studies on TpRu(L)(NCMe)-(Ph) [Tp = hydridotris(pyrazolyl)borate, L = CO, PMe 3 , P(Npyrrolyl) 3 , or P(OCH 2 ) 3 CEt] catalysts for olefin hydroarylation.…”
Section: à26mentioning
confidence: 99%
“…(28)]. [110] Both the Markovnikov selectivity for addition to propylene and the ortho/para selectivity observed for hydroarylation with toluene point to a Friedel-Crafts type of mechanism, which involves electrophilic activation of the olefin on coordination to platinum, and outer-sphere nucleophilic attack by the arene.…”
Section: Carbon Nucleophiles: Platinum-catalyzed Hydroarylation Of Almentioning
confidence: 99%
“…(28)]. [110] Die Markownikoff-Selektivität der Addition an Propylen und die ortho,para-Selektivität der Hydroarylierung mit Toluol deuten auf einen Friedel-Crafts-Mechanismus hin, der die elektrophile Aktivierung des Olefins bei Koordination zum Platin und den nucleophilen OuterSphere-Angriff durch das Aren einschließt. Widenhoefer et al haben über eine Methode zur Platinkatalysierten Hydroarylierung/Cyclisierung von Alkenylindolen zur Bildung von Tetrahydrocarbazolen berichtet [Gl.…”
Section: Kohlenstoff-nucleophile: Platin-katalysierte Hydroarylierungunclassified